Case report: Imported asymptomatic schistosomiasis among Belgian school travelers to Rwanda - Silvio Wallemacq; Ahalieyah Anantharajah; Pamela Baldin; Jean-Cyr Yombi; Jean-Cyr Yombi; Julien De Greef; Julien De Greef; Leïla Belkhir; Leïla Belkhir (Frontiers in Tropical Diseases, 2024)
Schistosomiasis is common in many tropical regions and poses a risk for the local population and travelers. In travelers, most of schistosomiasis are described as acute. We report the epidemiological, clinical, and laboratory characteristics associated with an outbreak of asymptomatic schistosomiasis among nonimmune Belgian school travelers in Rwanda. Schistosomiasis was diagnosed by serology in 12 out of the 15 (80%) travelers who swam in the lake nearly 2 years after a single exposure to freshwater at Kivu Lake, Rwanda. None showed signs of acute or chronic schistosomiasis. Eosinophilia was present in only 1 of them. Schistosoma mansoni eggs were not found in any infected patient. This report of an outbreak of asymptomatic schistosomiasis imported from Lake Kivu highlights the risk for travelers of acquiring the infection with only a short and single exposure, and provides strong arguments for routine serological screening for schistosomiasis in all individuals who have had any freshwater contact in endemic areas, irrespective of symptoms or laboratory findings.